The Electronic Journal of Oncology - Charles Dumontet (Issues in Science and Technology Librarianship)
This article reviews The Electronic Journal of Oncology, a non-profit, exclusively Internet-based journal containing original publications in the fields of oncology and hematology, freely accessible to physicians, paramedics and researchers having an interest in cancer. It contains peer reviewed original publications (reviews, clinical trials, fundamental research, case reports) in English which can be downloaded by readers.